Assessment of Pregnancy Complications among Internally Displaced Women in Karbala Governorate - Ridha M. lefta (Journal of Global Pharma Technology, 2020)
Background: Pregnant women face increased risks of complications as they exposure to displaced conflict zones with damaged and destroyed health facilities in out conflict zones. Objectives: To determine the pregnancy complications among displaced women, and to find out the relationship between dietary habits for displaced pregnancy and complication of pregnancy. Methodology: A descriptive analytic study has been conducted on non-probability purposive sample of (200) displaced pregnant women select AL-Hussein Teaching Hospital in Karbala governorate .This study has been conducted during the period of 1st December until (30)th December 2017. A questionnaire is used as a tool of data collection to fulfill the study. A content validity, which is carried out through 13 panel of experts. Validity is determined by a panel of experts while the reliability utilization its split half. A descriptive and inferential statistics are used to analyze the data. Results: This table shows that the study result for demographic data the majority of the study samples 21-25 years old are 32% and the most the sample related level of education have secondary school 38% and housewife are 93% and resident in urban. The study results indicate that the economic status sufficient to some extend and living at camp are 53%. This table depict that the complication among pregnancy displaced that indicate majority of pregnancy suffer from anemia is 49%. This table depict that the there is a non- significant between complication among pregnancy displace women and diatery habit domain at p. value more than 0.05. While there is a significant between complication pregnancy displaced and (dental problems and prenatal vitamin) at p. value less than 0.05, also the correlation between fregin food and complication pregnancy displaced women is high significant at p. value less than 0.01. Conclusion: Anemia is the major pregnancy complication among IDPs women. Recommendations: A special education programs focused on improvement the women knowledge and practices about the prevention and management of pregnancy complications. Keywords: Internally displacement, Pregnancy complications, Anemia, Prenatal vitamins, Dental problems.